RESULTADOS DO PROJETO DE PESQUISA EM MECATRÔNICA NA UNIJUÍ OBTIDOS EM 2008-2009 - Valdiero, Antonio C.; Rasia, Luiz A.; Bortolaia, Luis A.; Andrighetto, Pedro L.; Rafikov, Marat; Endler, Luciano; Miotto, Fabiane E. M.; Ritter, Carla S.; Locateli, Cristiano C.; Zago, Fernando; Schmitt, Paulo R. (Salão do Conhecimento, 2013)
Resumo